Work Motivation as a Moderator Between Work Environment and Ethical Leadership on Generation Z Employee Loyalty in Indonesia - Sofia Afriza Handayani; Fetty Poerwita Sary (Green Publisher Indonesia, 2025)
As a generation that grew up in the digital era with rapid technological advances and fast access to information, this affects their perspective on the workforce, shaping their expectations and values. This study focuses on the phenomenon of minimum loyalty from Generation Z employees in Indonesia, highlighting that their loyalty is significantly influenced by factors such as the work environment and ethical leadership. This research utilizes a quantitative approach, drawing on data from literature reviews and the distribution of questionnaires. This study employs Structural Equation Modeling (SEM), specifically the Smart Partial Least Squares (SmartPLS) method, to examine the direct relationship and mediating effects among variables. The results of this study suggest that the work environment has a significant impact on employee loyalty and work motivation. Additionally, there is a relationship between the work environment and ethical leadership, which fosters employee loyalty through increased work motivation. In conclusion, all hypotheses in this study are accepted, indicating that a good work environment and ethical leadership can enhance employee loyalty. The work environment and ethical leadership are closely correlated, enhancing work motivation and potentially leading to greater employee loyalty.